2019
DOI: 10.1007/s13238-019-0653-9
|View full text |Cite
|
Sign up to set email alerts
|

JMJD3 in the regulation of human diseases

Abstract: In recent years, many studies have shown that histone methylation plays an important role in maintaining the active and silent state of gene expression in human diseases. The Jumonji domain-containing protein D3 (JMJD3), specifically demethylate di- and trimethyl-lysine 27 on histone H3 (H3K27me2/3), has been widely studied in immune diseases, infectious diseases, cancer, developmental diseases, and aging related diseases. We will focus on the recent advances of JMJD3 function in human diseases, and looks ahea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 144 publications
(180 reference statements)
1
50
0
Order By: Relevance
“…Compared with the well-defined oncogenic and pro-fibrotic functions of EZH2, JMJD3 is a double-edged sword with complex and somehow opposite functions in different context of disease, tissue and cell type. Accumulating evidence have shown that JMJD3 plays pro-inflammatory or anti-inflammatory in immune diseases, and carcinogenic or tumor suppressive roles in various types of cancer, which is associated with the histone demythylase activity-dependent epigenetic regulation and its noncanonical noncatalytic functions 23 , 65 . As JMJD3 stimulates a wide range of genes implicated in inflammation, immunity, development, senescence and carcinogenesis, its expression in normal conditions is usually in low level in the organization, just as its undetectable expression in the tested hepatic cell lines in this study, its activation is an important host response against environmental and cellular stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the well-defined oncogenic and pro-fibrotic functions of EZH2, JMJD3 is a double-edged sword with complex and somehow opposite functions in different context of disease, tissue and cell type. Accumulating evidence have shown that JMJD3 plays pro-inflammatory or anti-inflammatory in immune diseases, and carcinogenic or tumor suppressive roles in various types of cancer, which is associated with the histone demythylase activity-dependent epigenetic regulation and its noncanonical noncatalytic functions 23 , 65 . As JMJD3 stimulates a wide range of genes implicated in inflammation, immunity, development, senescence and carcinogenesis, its expression in normal conditions is usually in low level in the organization, just as its undetectable expression in the tested hepatic cell lines in this study, its activation is an important host response against environmental and cellular stress.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of H3K27me2/3 methylation marks is specifically mediated by the JmjC domain-containing histone demethylases JMJD3 (KDM6B) and UTX (Ubiquitously transcribed Tetratricopeptide repeat on chromosome X) (KDM6A) 22 . JMJD3 is involved in cellular processes including differentiation, proliferation, senescence, and apoptosis, and thus is implicated in development and diseases 23 . JMJD3, UTX and EZH2 regulate hepatic plasticity inducing retro-differentiation and proliferation of hepatocytes 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, based on intensive studies across a broad spectrum of tumors 40 , 41 , the functional roles of both KDM6A and KDM6B in tumorigenesis were found to be highly cell type-specific and pathologic context-dependent. For instance, KDM6B could promote TGF-β-induced epithelial-mesenchymal transition (EMT) through activating SNAI1 in breast cancer cells 42 , and instigate proliferative, metastatic, and self-renewal capacities of tumor cells in liver, ovarian, and skin cancers by modulating multiple signalings 24 , 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…JMJD3 is upregulated in different human cancers, such as gliomas, breast cancer, and lung cancer. 30 33 Thus, it is a novel target for the treatment of various types of cancer. Previous studies, including our work, showed that JMJD3 plays an important role in cell fate commitment, such as cellular reprograming into the pluripotent state.…”
Section: Discussionmentioning
confidence: 99%